Ataxia with Parkinsonism and dystonia after intentional inhalation of liquefied petroleum gas - Godani M (Dove Medical Press, 2015)
Massimiliano Godani,1 Francesca Canavese,1 Sonia Migliorini,2 Massimo Del Sette1 1Neurology Unit, 2Department of Neuroradiology, Sant’Andrea Hospital, La Spezia, Italy Abstract: The practice of inhaling liquefied petroleum gas (LPG) to commit suicide is uncommon and almost exclusively a prerogative of the prison population. Numerous cases of sudden deaths caused by intentional propane and/or butane inhalation have been described, but these cases survived and a description of the consequences is very rare. We describe a prisoner who survived after voluntary inhalation of LPG, and who developed ataxia, Parkinsonism, and dystonia. Brain MRI showed bilateral hyperintensity in the basal ganglia and in the cerebellar hemispheres. The clinical evolution and the MRI abnormalities are similar to those described in cases of poisoning by CO where the mechanism of brain injury is related to histotoxic hypoxia. We believe that LPG, considered until now a mixture of gas with low neurotoxic power, may have caused direct toxic damage to the brain, mediated by a mechanism of hypoxia, such as in CO intoxication. Keywords: ataxia, Parkinsonism, dystonia, liquefied petroleum gas